Use of Hypotonic Maintenance Intravenous Fluids and Hospital-Acquired Hyponatremia Remain Common in Children Admitted to a General Pediatric Ward - Shukla, Shikha; Basu, Srikanta; Moritz, Michael L. (Frontiers in Pediatrics, 2016)
Aim: To evaluate maintenance intravenous fluid prescribing practices and the incidence of hospital-acquired hyponatremia in children admitted to a general pediatric ward. Methods: This is a prospective observational study conducted over a 2-month period in children ages 2 months to 5 years who were admitted to a general pediatric ward and who were receiving maintenance intravenous fluids. The composition, rate and duration of intravenous fluids was chosen at the discretion of the treating physician. Serum biochemistries were obtained at baseline and 24 hours following admission. Patients who were at high risk for developing hyponatremia or hypernatremia or had underlying chronic diseases or were receiving medications associated with a disorder in sodium and water homeostasis were excluded. Intravenous fluid composition and the incidence of hyponatremia (sodium < 135 mEq/L) were assessed. Results: Fifty-six children were enrolled. All received hypotonic fluids; 87.5% received 0.18% sodium chloride (NaCl) and 14.3% received 0.45% NaCl. Forty percent of patients (17/42) with a serum sodium less than 140 mEq/L experienced a fall in serum sodium with 12.5% of all patients (7/56) developing hospital-acquired or aggravated hyponatremia (126 – 134 mEq/L) with fall in serum sodium between 2 – 10 mEq/L. Conclusions: Administration of hypotonic fluids was a prevalent practice in children admitted to a general pediatric ward and is associated with acute hospital-acquired hyponatremia.